Titanium niobate material, preparation method thereof and battery
By doping fluorine ions and transition metal ions in titanium niobate materials, the problem of low electronic and ion conductivity of titanium niobate materials is solved, and the electrochemical performance and safety performance of the material are improved.
Patent Information
- Application Number
- CN202410275695.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-03-11
AI Technical Summary
The existing titanium niobate materials have low electronic and ionic conductivity, limiting their electrochemical properties.
By doping fluorine ions and transition metal ions in titanium niobate material, the doping of fluorine ions improves electron conductivity, the doping of transition metal ions increases the unit cell volume, and the diffusion rate of lithium ions is increased.
The co-doped titanium niobate material exhibits excellent electrochemical properties, including improved cycle stability and rate performance, while improving the safety performance of the material.
Smart Images

Figure CN118145705B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a titanium niobate material, a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion batteries (LIBs) are the most reliable power source for portable electronic devices and electric vehicles due to their high energy density and long cycle life. Graphite is a promising material due to its low cost and high specific capacity (372 mA hg -1 ) and has become a commonly used negative electrode material for commercial secondary lithium-ion batteries. However, due to the low operating voltage of graphite (0.1V vs Li+ / Li), the active lithium will be permanently consumed, and the formation of lithium dendrites and electrolyte interface film (SEI) on the graphite surface will cause safety problems. Therefore, new negative electrode materials are needed to meet this demand. Among the negative electrode intercalation materials, lithium titanate spinel is a "zero stress" material with a high operating voltage (1.55V vs Li+ / Li). These advantages make lithium titanate considered as a promising lithium-ion battery negative electrode material with long cycle stability and high safety. However, the theoretical specific capacity of lithium titanate is low (only 175mAh g -1 ), poor electrical conductivity, which hinders its large-scale practical application.
[0003] In recent years, niobium-based oxides have attracted much attention as high-capacity anode materials for lithium-ion batteries and are expected to replace lithium titanate. As a typical intercalation anode material, its excellent electrochemical performance is mainly attributed to the unique structure of titanium niobate, where the disordered arrangement of Nb atoms and Ti atoms occupies NbO 6 and TiO 6 The center of the octahedron. At the same time, NbO 6 Octahedron and TiO 6 The octahedrons share edges and vertices and form open tunnel-type gap spaces that can accommodate the transmission of lithium ions. Due to the structure of titanium niobate, the insertion and extraction of lithium ions are relatively easy, so it has excellent rate performance. Titanium niobate not only has the advantages of conventional lithium titanium materials in terms of cycle stability and long life, but also has the advantages of Ti 3+ / Ti 4+ , Nb 4+ / Nb 5+ and Nb 3+ / Nb 4+ Multiple redox pairs. It has a higher theoretical specific capacity (387.6 mAh g -1, much higher than lithium titanate, and even higher than graphite negative electrode), the working potential is similar to that of lithium titanate (1.6V vs Li+ / Li), which can effectively prevent the formation of lithium dendrites and the reduction and decomposition of the electrolyte. Compared with traditional batteries, the safety performance is greatly improved. However, titanium niobate also has some problems. The electronic and ionic conductivity of this material is low. Therefore, it is urgent to invent a method that can simultaneously improve the electronic and ionic conductivity of the material. Summary of the invention
[0004] The invention discloses a titanium niobate material, a preparation method thereof and a battery, so as to solve the problem that the existing titanium niobate material has low electronic and ionic conductivity.
[0005] In order to achieve the above purpose, the embodiments of this specification adopt the following technical solutions:
[0006] In a first aspect, a method for preparing a titanium niobate material is provided, comprising the following steps:
[0007] Dispersing a niobium source and a titanium source in a first solvent to obtain a first suspension;
[0008] Dispersing the compound containing fluorine ions and transition metal ions or the compound containing fluorine ions and the compound containing transition metal ions in a second solvent to obtain a second suspension;
[0009] The first suspension and the second suspension are mixed and calcined to obtain a titanium niobate material.
[0010] Optionally, in the step of dispersing the niobium source and the titanium source in the first solvent, the molar ratio of the niobium source to the titanium source is 1.9-2.15:1.
[0011] Optionally, the source of the fluoride ions is a combination of one or more of ammonium fluoride, ammonium bifluoride, iron fluoride and zinc fluoride.
[0012] Optionally, the transition metal ion is a metal ion whose ion radius is larger than that of the titanium ion.
[0013] Optionally, the transition metal ion is a combination of one or more of zinc, copper, zirconium and neodymium.
[0014] Optionally, in the step of dispersing the compound containing fluorine ions and transition metal ions or the compound containing fluorine ions and transition metal ions in the second solvent, the molar ratio of the fluorine ions to the transition metal ions is 1-2:1.
[0015] Optionally, the first solvent and the second solvent are respectively one or more of N,N-dimethylformamide, tetrahydrofuran, N-methylpyrrolidone, ethanol, and water; and / or
[0016] The transition metal ion-containing compound is a combination of one or more of zinc nitrate, copper oxide, zirconium oxide, neodymium oxide, iron fluoride, and zinc fluoride; and / or
[0017] The niobium source is a combination of one or more of niobium pentoxide, niobium chloride, niobium pentaethoxide, and niobium oxalate; and / or
[0018] The titanium source is one or a combination of one or more of titanium dioxide, titanium tetrachloride, tetrabutyl titanate, and titanium isopropoxide.
[0019] Optionally, in the step of dispersing the niobium source and the titanium source in the first solvent, the dispersion duration is 1-4 hours; and / or,
[0020] In the step of dispersing the compound containing fluorine ions and transition metal ions or the compound containing fluorine ions and transition metal ions in the second solvent, the dispersion lasts for 1-4 hours.
[0021] Optionally, in the step of mixing and calcining the first suspension and the second suspension, the duration of mixing the first suspension and the second suspension is 2-6 hours; and / or,
[0022] The calcination temperature is 800-1600°C; and / or,
[0023] The calcination duration is 6-48h.
[0024] In a second aspect, a titanium niobate material is provided, which is prepared by the preparation method described in any one of the first aspects.
[0025] In a third aspect, a battery is provided, comprising a negative electrode material formed by the titanium niobate material prepared by the preparation method described in any one of the first aspects or a negative electrode material formed by the titanium niobate material described in the second aspect.
[0026] At least one of the above technical solutions adopted in the embodiments of the present application can achieve the following beneficial effects:
[0027] According to the preparation method of the titanium niobate material of the present invention, fluorine and transition metal ions are used to synergistically dope the titanium niobate material. Fluorine ions are doped into oxygen sites to improve electrical conductivity. Doping with transition metal ions with larger radii increases the unit cell volume and improves the lithium ion diffusion rate. The synergistic effect of fluorine and transition metal ion doping improves the electronic and ionic conductivity of the titanium niobate material simultaneously, so that the titanium niobate material exhibits excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0029] Figure 1 This is an XRD comparison diagram of the titanium niobate material obtained according to Example 1 of the present invention and the undoped titanium niobate material of Comparative Example 1;
[0030] Figure 2 This is a comparison diagram of the first cycle charge and discharge curves of the titanium niobate material obtained according to Example 1 of the present invention and the undoped titanium niobate material of Comparative Example 1;
[0031] Figure 3 This is a ratio comparison diagram of the titanium niobate material obtained according to Example 1 of the present invention and the undoped titanium niobate material of Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the specific embodiments of the present application and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0033] According to one embodiment of the present application, a method for preparing a titanium niobate material is provided, comprising the following steps:
[0034] Dispersing a niobium source and a titanium source in a first solvent to obtain a first suspension;
[0035] Dispersing the compound containing fluorine ions and transition metal ions or the compound containing fluorine ions and the compound containing transition metal ions in a second solvent to obtain a second suspension;
[0036] The first suspension and the second suspension are mixed and calcined to obtain a titanium niobate material.
[0037] In the embodiments of this specification, the specific ratio of the niobium source and the titanium source is not limited by the present invention, as long as the effect of the present invention can be achieved. Optionally, in the step of dispersing the niobium source and the titanium source in the first solvent, the molar ratio of the niobium source and the titanium source is 1.9-2.15:1.
[0038] In the embodiments of this specification, the fluorine ion compound and the transition metal ion compound can be dispersed and mixed in the second solvent, or the fluorine ion and transition metal ion compound can be directly dispersed in the second solvent. The present invention does not limit the types of the fluorine ions and the transition metal ions, as long as the effects of the present invention can be achieved. Optionally, the source of the fluorine ions is a combination of one or more of ammonium fluoride, ammonium bifluoride, iron fluoride, and zinc fluoride. Optionally, the transition metal ion is a metal ion whose ionic radius is greater than that of the titanium ion. Preferably, the ionic radius of the transition metal ion is greater than that of the titanium ion. More preferably, the transition metal ion is a combination of one or more of zinc, copper, zirconium and neodymium. The source of the transition metal ion can be a combination of one or more of zinc nitrate, copper oxide, zirconium oxide, neodymium oxide, iron fluoride and zinc fluoride. The compound containing fluorine ions and transition metal ions can be a combination of one or more of iron fluoride and zinc fluoride.
[0039] In the embodiments of this specification, the types of the niobium source and the titanium source are not limited by the present invention, as long as the effect of the present invention can be achieved. Optionally, the niobium source is a combination of one or more of niobium pentoxide, niobium chloride, pentaethoxy niobium, and niobium oxalate. The titanium source is a combination of one or more of titanium dioxide, titanium tetrachloride, tetrabutyl titanate, and titanium isopropoxide.
[0040] In the embodiments of this specification, the specific ratio of the fluoride ion and the transition metal ion is not limited by the present invention, as long as the effect of the present invention can be achieved. Optionally, the molar ratio of the fluoride ion and the transition metal ion is 1-2:1.
[0041] In the embodiments of this specification, the present invention does not limit the types of the first solvent and the second solvent, as long as the effect of the present invention can be achieved. Optionally, the first solvent and the second solvent are a combination of one or more of N,N-dimethylformamide, tetrahydrofuran, N-methylpyrrolidone, ethanol, and water.
[0042] In the embodiments of this specification, in the step of dispersing the niobium source and the titanium source in the first solvent and in the step of dispersing the compound containing fluorine ions and transition metal ions or the compound containing fluorine ions and the compound containing transition metal ions in the second solvent, the dispersion time is not limited by the present invention, as long as a uniform dispersion effect can be achieved. Optionally, in the step of dispersing the niobium source and the titanium source in the first solvent, the dispersion duration is 1-4h. The dispersion duration is 1h, 2h, 3h, 4h or any value therebetween. In the step of dispersing the compound containing fluorine ions and transition metal ions or the compound containing fluorine ions and the compound containing transition metal ions in the second solvent, the dispersion duration is 1-4h. The dispersion duration is 1h, 2h, 3h, 4h or any value therebetween.
[0043] In the embodiment of this specification, in the step of mixing and calcining the first suspension and the second suspension, the mixing is achieved by magnetic stirring at room temperature. The mixing time is not limited by the present invention, as long as a uniform mixing effect can be achieved. Optionally, in the step of mixing and calcining the first suspension and the second suspension, the duration of mixing the first suspension and the second suspension is 2-6h. The duration of the mixing is 2h, 3h, 4h, 5h, 6h or any value therebetween. More preferably, the duration of the mixing is 4h.
[0044] In the embodiment of this specification, in the step of mixing and calcining the first suspension and the second suspension, the first suspension and the second suspension are mixed and then dried and calcined. The temperature of the drying is not limited by the present invention, as long as the drying effect can be achieved. Optionally, the drying temperature is 60-80°C. The drying temperature is 60°C, 65°C, 70°C, 75°C, 80°C or any value therebetween.
[0045] In the embodiment of this specification, in the step of mixing and calcining the first suspension and the second suspension, the calcination conditions are not limited by the present invention, as long as the calcination effect can be achieved. Optionally, the calcination temperature is 800-1600°C. The drying temperature is 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C or any value therebetween. More preferably, the drying temperature is 1250°C. Optionally, the duration of the calcination is 6-48h. The duration of the calcination is 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, 37h, 38h or any value therebetween. Optionally, the atmosphere during the calcination is a combination of one or more of oxygen, nitrogen, air and argon atmospheres.
[0046] In the titanium niobate material of the present invention, the fluorine ions can be doped into the oxygen sites to improve the electronic conductivity. The radius of fluorine ions is smaller than that of chlorine and bromide ions, and smaller than that of oxygen. It can relatively easily replace part of the oxygen, so that part of Ti and Nb are transformed into a low-valent state, which significantly improves the electronic conductivity. Doping with transition metal ions of larger radius can expand the interlayer spacing of titanium niobate, provide more space for lithium ion diffusion, and improve the lithium ion diffusion rate. The synergistic effect of fluorine and transition metal ion doping makes the ionic and electronic conductivity of titanium niobate materials synergistically improved without sacrificing compaction density and energy density, greatly improving the material's cycle stability and rate performance.
[0047] According to one embodiment of the present application, a titanium niobate material is provided, which is prepared by the preparation method described above.
[0048] According to one embodiment of the present application, a battery is provided, the battery comprising a negative electrode material formed by the titanium niobate material prepared by the preparation method described above or a negative electrode material formed by the titanium niobate material prepared as described above.
[0049] In the embodiment of the present specification, the battery includes a negative electrode material, and the negative electrode material includes a titanium niobate material, a conductive agent, and a binder, wherein the titanium niobate material accounts for 90-99% of the total mass of the negative electrode material, the conductive agent accounts for 0.5-5% of the total mass of the negative electrode material, and the binder accounts for 0.5-5% of the total mass of the negative electrode material. More preferably, the mass ratio of the titanium niobate material, the conductive agent, and the binder is 96%:2%:2%.
[0050] In the embodiments of this specification, the negative electrode material may also include a solvent, and the titanium niobate material, the conductive agent, and the binder are dispersed in the solvent to form a negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector, dried, rolled, and punched to obtain a negative electrode sheet, which is then assembled into a button battery. In the embodiments of this specification, the types of the conductive agent, the binder, and the solvent are not limited by the present invention, as long as the effect of the battery of the present invention can be achieved. Optionally, the binder is polyvinylidene fluoride PVDF, the conductive agent is acetylene black, and the solvent is N-methylpyrrolidone NMP.
[0051] The preparation method of the present invention is simple to operate, low in cost, and has low requirements for equipment. The prepared fluorine and transition metal ion co-doped titanium niobate material is in the form of micron short rods. In the co-doped titanium niobate material, fluorine ion doping replaces part of oxygen, so that Ti and Nb are transformed into a low-valence state, and the electronic conductivity is improved; transition metal ion doping increases the unit cell size and improves the lithium ion conduction rate of the material. The synergistic effect of anions and cations simultaneously improves the ion and electronic conductivity of the titanium niobate material, thereby further improving the cycle stability and rate performance of titanium niobate, and promoting the application of titanium niobate materials in the high-power field.
[0052] The technical solutions provided by various embodiments of the present application are described in detail below in conjunction with the accompanying drawings.
[0053] Embodiment 1:
[0054] A method for preparing a battery is provided, comprising the following steps:
[0055] (1) adding 0.799 g of titanium dioxide and 2.658 g of niobium pentoxide to 50 ml of ethanol solution for dispersion, and magnetically stirring for 2 h to uniformly mix the titanium dioxide and niobium pentoxide in the ethanol solution to obtain a first suspension;
[0056] (2) adding 0.0081 g of zinc chloride and 0.0037 g of ammonium fluoride to 10 ml of ethanol solution and dispersing them, and also magnetically stirring for 2 h to uniformly mix the zinc chloride and ammonium fluoride in the ethanol solution to obtain a second suspension;
[0057] (3) The first suspension and the second suspension were mixed, magnetically stirred at room temperature for 4 h, and then transferred to a forced air drying oven at 80° C. for drying. The mixture was then transferred to a tube furnace, calcined at 1250° C. for 24 h in an air atmosphere at a heating rate of 5° C. / min, and naturally cooled to room temperature to obtain a titanium niobate material co-doped with fluorine and transition metal ions.
[0058] (4) Titanium niobate material, acetylene black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling and punching, a negative electrode sheet is obtained, which is then assembled into a button cell; wherein the mass ratio of titanium niobate material, acetylene black and polyvinylidene fluoride is 96%:2%:2%.
[0059] Embodiment 2:
[0060] A method for preparing a battery is provided, comprising the following steps:
[0061] (1) adding 0.799 g of titanium dioxide and 2.658 g of niobium pentoxide to 50 ml of ethanol solution for dispersion, and magnetically stirring for 2 h to uniformly mix the titanium dioxide and niobium pentoxide in the ethanol solution to obtain a first suspension;
[0062] (2) adding 0.0081 g of neodymium chloride and 0.0037 g of ammonium fluoride to 10 ml of ethanol solution for dispersion, and also magnetically stirring for 2 h to uniformly mix zinc chloride and ammonium fluoride in the ethanol solution to obtain a second suspension;
[0063] (3) The first suspension and the second suspension were mixed, magnetically stirred at room temperature for 4 h, and then transferred to a forced air drying oven at 80° C. for drying. The mixture was then transferred to a tube furnace, calcined at 1250° C. for 24 h in an air atmosphere at a heating rate of 5° C. / min, and naturally cooled to room temperature to obtain a titanium niobate material co-doped with fluorine and transition metal ions.
[0064] (4) Titanium niobate material, acetylene black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling and punching, a negative electrode sheet is obtained, which is then assembled into a button cell; wherein the mass ratio of titanium niobate material, acetylene black and polyvinylidene fluoride is 96%:2%:2%.
[0065] In Example 2, neodymium ions are used as transition metal ions. Neodymium ions have a larger radius, forming a wider lithium ion diffusion channel, further improving the lithium ion transmission rate.
[0066] Embodiment 3:
[0067] A method for preparing a battery is provided, comprising the following steps:
[0068] (1) adding 0.799 g of titanium dioxide and 2.658 g of niobium pentoxide to 50 ml of ethanol solution for dispersion, and magnetically stirring for 2 h to uniformly mix the titanium dioxide and niobium pentoxide in the ethanol solution to obtain a first suspension;
[0069] (2) adding 0.0081 g of zinc chloride and 0.0037 g of ammonium fluoride to 10 ml of ethanol solution and dispersing them, and also magnetically stirring for 2 h to uniformly mix the zinc chloride and ammonium fluoride in the ethanol solution to obtain a second suspension;
[0070] (3) The first suspension and the second suspension were mixed, magnetically stirred at room temperature for 4 h, and then transferred to a forced air drying oven at 80° C. for drying. The mixture was then transferred to a tube furnace, calcined at 1250° C. for 12 h in an air atmosphere at a heating rate of 5° C. / min, and naturally cooled to room temperature to obtain a titanium niobate material co-doped with fluorine and transition metal ions.
[0071] (4) Titanium niobate material, acetylene black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling and punching, a negative electrode sheet is obtained, which is then assembled into a button cell; wherein the mass ratio of titanium niobate material, acetylene black and polyvinylidene fluoride is 96%:2%:2%.
[0072] In Example 3, the calcination time is shortened, which is beneficial to reducing the industrial production cost.
[0073] Embodiment 4:
[0074] A method for preparing a battery is provided, comprising the following steps:
[0075] (1) adding 0.799 g of titanium dioxide and 2.658 g of niobium pentoxide to 50 ml of ethanol solution for dispersion, and magnetically stirring for 2 h to uniformly mix the titanium dioxide and niobium pentoxide in the ethanol solution to obtain a first suspension;
[0076] (2) adding 0.0081 g of zinc chloride and 0.0037 g of ammonium bifluoride to 10 ml of ethanol solution and dispersing them, and stirring them magnetically for 2 h to uniformly mix the zinc chloride and ammonium fluoride in the ethanol solution to obtain a second suspension;
[0077] (3) The first suspension and the second suspension were mixed, magnetically stirred at room temperature for 4 h, and then transferred to a forced air drying oven at 80° C. for drying. The mixture was then transferred to a tube furnace, calcined at 1250° C. for 24 h in an air atmosphere at a heating rate of 5° C. / min, and naturally cooled to room temperature to obtain a titanium niobate material co-doped with fluorine and transition metal ions.
[0078] (4) Titanium niobate material, acetylene black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling and punching, a negative electrode sheet is obtained, which is then assembled into a button cell; wherein the mass ratio of titanium niobate material, acetylene black and polyvinylidene fluoride is 96%:2%:2%.
[0079] Comparative Example 1:
[0080] A method for preparing a battery is provided, comprising the following steps:
[0081] (1) adding 0.799 g of titanium dioxide and 2.658 g of niobium pentoxide to 50 ml of ethanol solution for dispersion, and magnetically stirring for 2 h to uniformly mix the titanium dioxide and niobium pentoxide in the ethanol solution to obtain a first suspension;
[0082] (2) The first suspension was transferred to a forced air drying oven at 80° C. for drying. The suspension was then transferred to a tube furnace and calcined at 1250° C. for 24 h in an air atmosphere at a heating rate of 5° C. / min. The suspension was naturally cooled to room temperature to obtain an undoped titanium niobate material.
[0083] (3) Titanium niobate material, acetylene black and polyvinylidene fluoride are dispersed in N-methylpyrrolidone to form a negative electrode slurry, the negative electrode slurry is coated on the negative electrode collector, dried, rolled and punched to obtain a negative electrode sheet, and then assembled into a button battery; wherein the mass ratio of titanium niobate material, acetylene black and polyvinylidene fluoride is 96%:2%:2%.
[0084] Test method:
[0085] X-ray diffraction (XRD) is a very useful technique for analyzing the crystal structure of a substance. When X-rays pass through a substance, they will diffract. This diffraction is caused by the interaction between the X-rays and the atoms and ions inside the substance. When the atomic arrangement in the X-ray crystal structure meets certain conditions, the peak position presented by the diffraction corresponds to a certain crystal plane spacing. The X-ray diffraction spectrum refers to the intensity and corresponding position spectrum of the X-ray diffraction produced when the crystals in the substance are irradiated. :By analyzing the X-ray diffraction spectrum, the crystal structure information of the substance, such as unit cell parameters, crystal symmetry, lattice defects, etc., can be determined. This test uses an X-ray diffractometer produced by the German company BRUKER to test the sample powder and electrode plates, and then refine them to obtain the unit cell parameters. The scanning speed is 10°min -1 ,The scanning range is 10°~80°.
[0086] Constant current charge-discharge test (Constant Current Charge-Discharge) is a commonly used analysis method for battery performance testing, which is used to determine the electrochemical parameters of the battery such as cycle performance, specific capacity, and voltage platform. This method can obtain a series of electrochemical information such as cycle stability, capacity retention rate, coulomb efficiency, rate charge and discharge performance, and charge and discharge characteristics. In this application, the new Wei charge and discharge tester CT-3008 was used for battery charge and discharge testing, and the voltage test range was 1.0~3.0V. The cycle performance test refers to 2 activations at 0.1C and then a long cycle test. The rate test refers to 5 cycle tests at different rates (0.2C, 0.5C, 1C, 2C, 5C, 10C, 20C, 40C, 0.2C) during the charge and discharge process. These test methods can comprehensively evaluate the electrochemical performance of the battery and provide important support for battery research and development.
[0087] Figure 1 This is an XRD comparison diagram of the synthesized fluorine and zinc co-doped titanium niobate material and the undoped titanium niobate material of comparative example 1. It can be seen that after doping, the peak position shifts to a small angle. According to the Bragg equation, it can be concluded that the lattice size of titanium niobate increases after doping, which is conducive to the rapid transmission of lithium ions. Figure 2 The first charge-discharge curve of the fluorine-zinc co-doped titanium niobate material obtained in this example at 0.1C, the discharge and charge reversible capacities are 270.9 and 260.5 mAh g -1 The first coulombic efficiency reached 96.1%, which is higher than the undoped titanium niobate material in comparative example 1. Figure 3 It can be seen that the rate performance of the fluorine and zinc co-doped titanium niobate material obtained in this embodiment is better than that of the undoped titanium niobate material in comparative example 1. The excellent performance of the anion-cation co-doped titanium niobate is due to the fact that the doping of transition metal ions with larger radii increases the unit cell volume and improves the diffusion rate of lithium ions, and the fluorine ions are doped into the oxygen sites, so that part of the titanium and niobium are transformed into a low-valent state, and the excess electrons are charged to compensate, thereby improving the conductivity. The synergistic effect of anions and cations enables the titanium niobate material to exhibit excellent electrochemical properties.
[0088] The present invention can utilize the performance of niobium-based oxide as a high-capacity anode material for lithium-ion batteries, and has excellent rate performance. Compared with traditional batteries, the safety performance is greatly improved. The method used to prepare titanium niobate materials based on fluorine and transition metal ion co-doping is simple in preparation process and low in cost. It can simultaneously improve the electronic and ionic conductivity of titanium niobate materials, thereby improving cycle stability and rate performance, and can be used in large-scale production.
[0089] In order to synergistically improve the electronic and ionic conductivity of titanium niobate materials without sacrificing compaction density and energy density, the present invention adopts a low-cost and easy-to-implement titanium niobate material modification scheme, which can help further commercial applications of titanium niobate materials and promote the development of cold-region energy storage.
[0090] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing titanium niobate material, characterized in that: The following steps are involved: Dispersing a niobium source and a titanium source in a first solvent to obtain a first suspension; dispersing a compound containing fluorine ions and transition metal ions in a second solvent to obtain a second suspension; The first suspension and the second suspension are mixed and calcined to obtain a titanium niobate material; Wherein, the compound containing fluoride ions and transition metal ions is one or a combination of two of iron fluoride and zinc fluoride.
2. The preparation method according to claim 1, characterized in that: In the step of dispersing the niobium source and the titanium source in the first solvent, the molar ratio of the niobium source to the titanium source is 1.9-2.15:
1.
3. The preparation method according to claim 1, characterized in that: In the step of dispersing the compound containing fluoride ions and transition metal ions in the second solvent, the molar ratio of the fluoride ions to the transition metal ions is 1-2:
1.
4. The preparation method according to claim 1, characterized in that: The first solvent and the second solvent are respectively one or more of N,N-dimethylformamide, tetrahydrofuran, N-methylpyrrolidone, ethanol, and water; and / or The niobium source is a combination of one or more of niobium pentoxide, niobium chloride, niobium pentaethoxide, and niobium oxalate; and / or The titanium source is one or a combination of one or more of titanium dioxide, titanium tetrachloride, tetrabutyl titanate, and titanium isopropoxide.
5. The preparation method according to claim 1, characterized in that: In the step of dispersing the niobium source and the titanium source in the first solvent, the dispersion lasts for 1-4 hours; and / or, In the step of dispersing the compound containing fluorine ions and transition metal ions in the second solvent, the dispersion lasts for 1-4 hours.
6. The preparation method according to claim 1, characterized in that: In the step of mixing and calcining the first suspension and the second suspension, the duration of mixing the first suspension and the second suspension is 2-6 hours; and / or, The calcination temperature is 800-1600°C; and / or, The calcination duration is 6-48 h.
7. A titanium niobate material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 6.
8. A battery, characterized in that: The battery comprises a negative electrode material formed by the titanium niobate material prepared by the preparation method described in any one of claims 1 to 6 or a negative electrode material formed by the titanium niobate material described in claim 7.
Citation Information
Patent Citations
Anode material for lithium ion battery and preparation method thereof
TW202125881A
Active electrode material
WO2024127010A1